Studi Potensi dan Dampak Aktivitas Wisata Sungai Batang Gadis di Kota Panyabungan Kabupaten Mandailing Natal Study Of Potency And Analysis Of The Impact Of Tourism Activities On Water Quality Batang Gadis River District Mandailing Natal Of Panyabungan - Rizky Amalia Putri; Pindi Patana; Ani Suryanti (AQUACOASTMARINE, 2015)
River is one of the most important natural resources for human, due to it’s a source of drinking water, tourism, animal husbandry, and fishery. Positive impact of tourism activities in economic development can also lead to negative effects of environmental degradation. Research conducted at District Mandailing Natal of Panyabungan, in May – August 2014 by analyzing water quality of Batang Gadis River and perceptions of visitors and managers. The results showed that water quality value for eight parameters of Batang Gadis River was under quality based on PP No 82 tahun 2001. Visitors felt comfortably with the attractions. Batang Gadis River has great tourism Potency for develop with properness 79,25 % .Key Words : Colifaecal, Water Quality, Potency of Tourism, Batang Gadis River, Tourism.